The scientific profiles of documented collections via publication data: Past, present, and future directions in forensic anthropology - Alves-Cardoso, Francisca; Campanacho, Vanessa (MDPI, 2022)
Human osteological documented collections (DCs), also referred to as “identified collections”, are a valuable resource in biological and forensic anthropology, as they offer the possibility for hypothesis-driven research on sex and age-at-death estimation methods, human variability, and other morphometric-based parameters of individual identification. Consequently, they feature in many publications addressing the forensic sciences. The paper aims to explore the scientific profiles of DCs via publication using bibliometric data. The Dimensions databases were used to select the DC-related keywords in the title and abstracts of the publications. The search result analysis and extraction were conducted using VOSviewer. A total of 376 articles were found, published between 1969 and 2021 (November). The number of publications has increased over the years, specifically after 2011. The results show that most of the publications are associated with countries such as the United States and Portugal (the latter highlights the University of Coimbra), that the research tends to focus on human biological profiling (e.g., age, sex assessments), and that the journals with the highest numbers of publications were related to forensic sciences. This analysis shows a positive correlation between DC publications and the growth of forensic anthropology in recent years, with a slight shift towards the leading institutions that publish DC-based research. Hence, we can anticipate a change in the institutional leading profiles in the years to come.
This article belongs to the Collection The Rise of Forensic Anthropology and Documented Human Osteological Collections
Keywords: identified skeletal collections; human skeleton; bibliometric data; research networks; ethics